2011 37th IEEE Photovoltaic Specialists Conference 2011
DOI: 10.1109/pvsc.2011.6186581
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced optical absorbance of epitaxial emitter silicon solar cells with a back germanium epilayer

Abstract: Direct germanium (Ge) epilayer growth on silicon (Si) solar cells offers the potential of improving the power conversion efficiency (PCE) as a result of enhancement in optical absorbance, particularly at longer wavelength. The realization of this potential depends critically on the competing effects between the short circuit current density (JSC) gain due to the improved infrared absorption and the reduction in open circuit voltage (VOC) due to smaller bandgap in the Ge layer, as well as imperfection at the Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Inside the reactor, the substrates were heated in-situ in ultra pure H 2 at 1100°C to remove the native surface oxides. From a previous study, [58] an open-circuit voltage (V oc ) degradation of the solar cell was observed when the back Ge epilayer was grown after epitaxial growth of the n-Si emitter. To rectify this issue, the growth sequence of Si and Ge epilayers was reversed.…”
mentioning
confidence: 99%
“…Inside the reactor, the substrates were heated in-situ in ultra pure H 2 at 1100°C to remove the native surface oxides. From a previous study, [58] an open-circuit voltage (V oc ) degradation of the solar cell was observed when the back Ge epilayer was grown after epitaxial growth of the n-Si emitter. To rectify this issue, the growth sequence of Si and Ge epilayers was reversed.…”
mentioning
confidence: 99%